Taxonomy, biostratigraphy, and phylogeny of Eocene Turborotalia - P. N. Pearson; V. Premec Fucek; I. Premoli Silva (Cushman Foundation for Foraminiferal Research, 2006)
The taxonomy, phylogeny and biostratigraphy of Eocene Turborotalia is reviewed. A total of nine species are recognized as distinct, namely Turborotalia altispiroides Bermudez, 1961, Turborotalia ampliapertura (Bolli, 1957), Turborotalia cerroazulensis (Cole, 1928), Turborotalia cocoaensis (Cushman, 1928), Turborotalia cunialensis (Toumarkine and Bolli, 1970), Turborotalia frontosa (Subbotina, 1953), Turborotalia increbescens (Bandy, 1949), Turborotalia pomeroli (Toumarkine and Bolli, 1970), and Turborotalia possagnoensis (Toumarkine and Bolli, 1970). We support the view of Samuel and Salaj (1968) and Toumarkine and Bolli (1970) that Turborotalia frontosa, an enigmatic species that evolved in the early Eocene, was the first true member of the genus. Despite having a more globular morphology, T. frontosa shares several characters with other members of the genus, including its pustulose wall which has a strong tendency to defoliate, and high arched aperture. There is also a complete morphological intergradation between T. frontosa and later species of the genus. Studies of wall texture and ontogeny (Hemleben and Olsson Chapter 4, this volume) reveal the similarity of neanic T. frontosa with adult Globanomalina australiformis, a high latitude species that first evolved in the late Paleocene. We hypothesize that T. frontosa was descended from Globanomalina australiformis by the heterochronic process of hypermorphosis, and hence include Turborotalia in the Family Hedbergellidae.